Il paesaggio come commons. Riflessioni teoriche e analisi empiriche: il caso del Parco Paduli nel Salento delle Serre - Mariateresa Gattullo (Bollettino della Società Geografica Italiana)
Unlike some categories of goods, it becomes more difficult to qualify landscape as commons. This study intends to discover the possible similarities and differences between traditional commons and landscape. The aim is to demonstrate that, although landscape is neither rival nor excludible, it can be self sustainable managed and preserved only if treated as commons. In this way, the case study analyses a neglected landscape located in Apulia, precisely in the area of Salento delle Serre (Parco Paduli) administratively within the Union of Municipalities called Terre di Mezzo.